2018
DOI: 10.1016/j.kontakt.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards communication skills among nursing students and its association with sense of coherence

Abstract: The aim of the study is to examine the relationships between attitudes towards communication skills, self-evaluation of communication abilities, and sense of coherence among students of nursing. A cross-sectional correlational study design was employed. Altogether, 227 university nursing students participated in the study (20.53 ± 2.04; 96.9% females). Communication Skills Attitudes Scale (CSAS), Sense of Coherence Scale (SOC), and short self-evaluation scale of communication ability of own design were used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Moderate positive attitudes towards learning communication skills among nursing students is supported by a study conducted recently among 227 University nursing students in Martin. [30] In addition, strong disagreement with the statement "I don't need good communication skills to be a nurse" indicate a positive perception of the importance of communication skills in the practice among students. These results are in accordance with the research study of Busch et al [31] where low negative attitudes towards communication skills and moderate positive attitudes were found among medical students in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate positive attitudes towards learning communication skills among nursing students is supported by a study conducted recently among 227 University nursing students in Martin. [30] In addition, strong disagreement with the statement "I don't need good communication skills to be a nurse" indicate a positive perception of the importance of communication skills in the practice among students. These results are in accordance with the research study of Busch et al [31] where low negative attitudes towards communication skills and moderate positive attitudes were found among medical students in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the intervention made a positive contribution to the development of students' attitudes towards communication and communication knowledge. Previous research using computer simulated-based interactive communication education has not included assessment of communication attitudes as a learning outcome ( Choi et al, 2020 ), however positive communication attitudes are associated with nursing students' positive perception of their ability to use existing resources ( Skodova et al, 2018 ). Adequate communication education is not provided in undergraduate nursing textbooks used in the United States ( Carmack and Harville, 2019 ), with content that makes cursory mention of communication without dissecting its components, vocabulary, and the evidence associated with the science of communication.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic communication is based on the knowledge, attitudes, and skills of the patient and nurse that lead to patient understanding and participation ( Abdolrahimi et al, 2017b ). Despite this, most studies have focused on communication skills, communication knowledge, and medical students ( Epstein et al, 2010 ; Škodová et al, 2018 ). There is not a comprehensive assessment of attitudes in the communication of nursing students before they are exposed to real human interactions during their clinical practice ( Foronda et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioral component of attitudes is a manifestation of the underlying cognitive and affective components ( Anvik et al, 2007 ). This aspect is very important in nursing students because assessment of ACO allows identification of negative attitudes and perception of communication is an unimportant part of effective healthcare, which could negatively influence the effectiveness of the educational process ( Škodová et al, 2018 ) in the integration of communicative knowledge and skills in nursing students ( Fukada, 2018 ). In addition, studying ACO within the care process helps to evaluate the interpersonal communication of the nurse with the patient ( Chan, 2017 ) in order to be able to adapt strategies and their effectiveness ( Grant and Jenkins, 2014 ) to increase the quality of patient care and well-being of nursing students ( Satu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation